Defining clinical decision making in the provision of audio-visual outpatient care for acute upper limb trauma services: A review of practice. Issue 2 (February 2021) - McMullen, E.J.; Robson, M.; Valand, P.; Sayed, L.; Steele, J.
Summary: The Covid-19 pandemic has accelerated the widespread adoption of technology-enabled care in the NHS. 1 Moving into phase two of the response, the continuing use of audio-visual technology is expected, where appropriate, to be integral in the provision of safe, quality patient care. 2 A clinical need therefore exists to identify when care can be safely delivered remotely using audio-visual technology and when there is a need for in-person contact. At Salisbury Foundation Trust (SFT), during phase one of the NHS response to Covid-19, the decision to treat upper limb trauma patients in-person or remotely was made using clinical screening criteria. For many patients, audio-visual appointments offered a practical, time efficient way of accessing their reconstructive team for assessment, advice and post-operative care. However, a subset of patients was identified by the team as requiring at least one in-person consultation to minimize perceived clinical risk and to optimize quality outcomes. In order to understand more fully the challenges and successes of technology-enabled care to date, a national survey of practice across hand units in the UK was conducted. We present here some of our key findings and propose the need to develop nationally agreed screening criteria to determine how and when technology enabled outpatient care can be used in the management of acute upper limb trauma. The results of this survey forms part of a series of projects currently underway looking at the efficacy of audio-visual care in upper limb trauma, including a multicentre observational study.